THE EFFECT OF USING YOUTUBE VIDEO ON THE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT AT THE SEVENTH GRADE OF SMP SWASTA TELADAN PEMATANGSIANTAR - Turnip, Roni; Silalahi, Dumaris Elseria; Munthe, Melda Veby Ristella (Dharmas Education Journal (DE_Journal), 2024)
The purpose of this study is to find out the impact of using YouTube videos on the procedural writing skills of seventh grade students at SMP Swasta Teladan Pematangsiantar. This study focuses on the use of YouTube videos as a tool for students' writing on the topic “Making a Drink.” This study uses quantitative research with a quasi-experimental research design from Creswell. The population of this study consisted of seventh grade students of SMP Swasta Teladan Pematangsiantar, a total of 64 students. The sample of this study was divided into two groups, namely the experimental class (VII-A), consisting of 32 students who used YouTube video as a medium, and the control class (VII-B), consisting of 32 students who used only the teacher's explanation. Data were collected using writing tests for the pre-test and the final test. The researcher found that the mean of the pre-test was 52.6 in the experimental group and 56.2 in the control group. The mean of the final test in the experimental group was 75.8 and 72.1 in the control group. The t-value was determined to be 2.416, while the t-value based on degrees of freedom (df) was 1.670 for a significance level of 0.05. Since the t-value is greater than the t-value (2.416>1.671). Therefore, it can be concluded that YouTube videos have a significant impact on seventh-grade students' ability of SMP Swasta Teladan Pematangsiantar to write procedural texts.